Short-Duration Maximal and Long-Duration Submaximal Effort Forearm Exercise Achieve Elevations in Serum Brain-Derived Neurotrophic Factor - Walsh, Jeremy J.; Bentley, Robert F.; Gurd, Brendon J.; Tschakovsky, Michael E. (Frontiers in Physiology, 2017)
Brain-derived neurotrophic factor (BDNF) is a major orchestrator of exercise-induced brain plasticity and circulating (peripheral) BDNF may have central effects. Approximately 99% of circulating BDNF is platelet-bound, and at rest 30% of circulating platelets are stored in the spleen. Interestingly, forearm handgrip exercise significantly elevates sympathetic outflow and has been shown to induce splenic constriction, suggesting that small muscle mass exercise could stand as a viable strategy for increasing circulating BDNF; however, the BDNF response to handgrip exercise is currently unknown. Purpose: This study examined BDNF and platelet responses to short-duration maximal (ME) and prolonged submaximal (SE) effort handgrip exercise. Methods: Healthy males (n=18; 21.4 2.1 years, BMI 25.0 1.0 kg/m2) performed 10 minutes of ME and 30 minutes of SE. Blood was sampled for the determination of serum BDNF and platelet count at rest and during the last minute of exercise. Results: Compared to rest, serum BDNF significantly increased during ME (21.2%) and SE (11.2%), which displayed a non-significant trend towards an intensity-dependent response. Platelets increased in an intensity-dependent fashion compared to rest with an 8.0% increase during ME and 3.1% during SE, and these responses were significantly correlated with diastolic blood pressure responses to handgrip exercise. Further, the amount of BDNF per platelet significantly increased compared to rest during ME (13.4%) and SE (8.7%). Conclusions: Handgrip exercise evokes physiologically meaningful significant increases in serum BDNF and platelets, implicating splenic constriction as a key mechanism and confirming efficacy of this exercise model for elevating circulating BDNF.